2012
DOI: 10.1007/s10552-012-9971-4
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and cancer II: role of diabetes medications and influence of shared risk factors

Abstract: An association between type 2 diabetes mellitus (DM) and cancer has long been postulated, but the biological mechanism responsible for this association has not been defined. In part one of this review, we discussed the epidemiological evidence for increased risk of cancer, decreased cancer survival, and decreased rates of cancer screening in diabetic patients. Here we review the risk factors shared by cancer and DM and how DM medications play a role in altering cancer risk. Hyperinsulinemia stands out as a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 144 publications
(219 reference statements)
5
67
0
2
Order By: Relevance
“…It has been postulated that insulin resistance and hyperglycemia may induce the development of colorectal cancer and conventional adenomas through inflammatory mechanisms, production of oxidative stress or through involvement in the proliferative pathways as in the case of insulin-like growth factor (IGF) pathway [26,27]. Regarding SSA/Ps and their association with diabetes mellitus, there is only one study from Anderson et al indicating a positive association [9].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that insulin resistance and hyperglycemia may induce the development of colorectal cancer and conventional adenomas through inflammatory mechanisms, production of oxidative stress or through involvement in the proliferative pathways as in the case of insulin-like growth factor (IGF) pathway [26,27]. Regarding SSA/Ps and their association with diabetes mellitus, there is only one study from Anderson et al indicating a positive association [9].…”
Section: Discussionmentioning
confidence: 99%
“…19 We therefore took particular interest in determining if duration of diabetes was independently associated with cancer survivorship and found that this was not the case. This latter finding suggests that diabetes-related factors of control and complications may not be key factors influencing cancer survivorship but contribute simply to the burden of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the complex nature of diabetes and the broad array of available therapies, it is difficult, in observational settings, to discern whether the inverse association between metformin and cancer risk is due to an anti-neoplastic effect of metformin or might result from uncontrolled confounding, when metformin is compared to other antidiabetics [208,[216][217][218]. Several trials have recently been launched that aim to assess the potential of metformin for preventing cancer or cancer recurrence [208,215].…”
Section: Metforminmentioning
confidence: 99%